Buckling design of large eccentrically filled steel silos - Cao, Qing-shuai; Zhao, Yang (Powder technology, 2018)
Large steel silos are typical kinds of thin-walled structure which are widely used for storing huge quantities of granular solids in industry and agriculture. In the present analyses, buckling design of circular steel silos subject to large eccentricity filling pressure is demonstrated in accordance with Eurocode: EN1990, 1991, 1993 . The finite element model is established by using the commercial general purpose computer package ANSYS. Five types of buckling analyses are carried out for the geometrically perfect and imperfect models, with and without the consideration of the material plasticity, which are designated as LBA, GNA, GMNA, GNIA, and GMNIA in EN 1993 Part 1–6. Buckling behavior of five example steel silos with capacity of 40,000 to 60,000m3 is investigated whose slenderness ranges from 1.89 to 0.46, comprising intermediate slender and squat silos widely applicable in practical engineering. The results show that the buckling deformations are nonsymmetrical and the GMNIA analysis gives out the least buckling load factor for all example silos from all proposed buckling analysis types, and the load displacement curves are highly nonlinear and predict a distinct maximum load followed by a descending path, in which the maximum load is taken as the critical buckling point λcr for the equilibrium path. The buckling mode in GMNIA analysis takes the form of the well-known elephant-foot deformation at the bottom part of the shell wall, combined with nonsymmetrical waves in meridional direction throughout the whole height of the silo wall due to the distribution of weld imperfection. The geometrical nonlinearity is beneficial while material nonlinearity is strong and detrimental to buckling behavior of example silos. The effect of weld imperfection is also harmful to buckling resistance of silo, which is more serious for relatively slender silos than squat silos. The buckling is mainly governed by the nonuniform distribution of the solid pressure other than other influential factors as the weld imperfection, geometrical and material nonlinearity, compared with the load case of symmetrical filling. The economical design of steel silos can be effectively measured by the economic index called the ratio of capacity to steel consumption (RCS). It is validated that the index RCS increases rapidly with the decrease of silo slenderness, and the storage efficiency of example silos is increased by about 2.1 times with the slenderness varying from 1.89 to 0.46. It also suggests that the eccentricity in filling of steel silo should be reduced as far as possible for improvement of buckling strength of structure under eccentric filling. Large eccentrically filled steel silo. [Display omitted] •Buckling of large steel silo subject to large eccentricity filling pressure is evaluated.•Five types of buckling are undertaken for geometrically perfect and imperfect models.•Effects of nonlinearity and weld imperfection on buckling strength and mode are investigated.•Eccentricity in filling silo should be reduced at any possible for improvement of buckling strength.